The germline p53 activation syndrome: A new patient further refines the clinical phenotype. Issue 7 (1st April 2022) - Kumar, Runjun D.; Tosur, Mustafa; Lalani, Seema R.; Mahoney, Donald H.; Bertuch, Alison A.
Abstract: The tumor suppressor p53 has well known roles in cancer development and germline cancer predisposition disorders, but increasing evidence supports the role of activation of this transcription factor in the pathogenesis of inherited bone marrow failure and chromosomal instability disorders. Here we report a patient with red cell aplasia, which was steroid responsive, as well as intellectual disability, seizures, microcephaly, short stature, cellular radiosensitivity, and normal telomere lengths, who had a germline heterozygous C‐terminal frameshift variant in TP53 similar to others that activate the transcription factor. This is the third reported individual with a germline p53 activation syndrome, with several unique features that refine the clinical disease associated with these variants.